2015
DOI: 10.1007/s11481-015-9609-x
|View full text |Cite
|
Sign up to set email alerts
|

A Basal Tone of 2-Arachidonoylglycerol Contributes to Early Oligodendrocyte Progenitor Proliferation by Activating Phosphatidylinositol 3-Kinase (PI3K)/AKT and the Mammalian Target of Rapamycin (MTOR) Pathways

Abstract: A basal tone of the endocannabinoid 2-arachidonoylglycerol (2-AG) enhances late oligodendrocyte progenitor cell (OPC) differentiation. Here, we investigated whether endogenous 2-AG may also promote OPC proliferation in earlier stages. We found that the blockade of 2-AG synthesizing enzymes, sn-1-diacylglycerol lipases α and β (DAGLs), with RHC-80267 or the antagonism of either CB1 or CB2 cannabinoid receptors with AM281 and AM630, respectively, impaired early OPC proliferation stimulated by platelet-derived gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 26 publications
(40 reference statements)
4
28
0
2
Order By: Relevance
“…CB 1 receptor activation influences multiple effector systems; because of its wide distribution in the brain, the CB 1 receptor is believed to be responsible for mediating the majority of the cannabinoids' effects in the CNS (Cabral and Marciano-Cabral, 2005;Di Marzo, 2009). Evidence obtained by multiple groups supports the hypothesis that the CB 1 receptor plays a key role in various cellular events (Ferreira-Vieira et al, 2014;Gomez et al, 2015;Zhang et al, 2015). Moreover, it has been reported that the CB 1 receptor is involved in cognitive and affective processes, as well as in the control of motor activity, stress, addiction, and neuroprotection (Nagayama et al, 1999;Broadbent et al, 2004;Finn, 2010;Naydenov et al, 2014;McReynolds et al, 2016).…”
Section: Cb 1 Receptor: Pharmacology and Cell Signaling Pathwaysmentioning
confidence: 95%
“…CB 1 receptor activation influences multiple effector systems; because of its wide distribution in the brain, the CB 1 receptor is believed to be responsible for mediating the majority of the cannabinoids' effects in the CNS (Cabral and Marciano-Cabral, 2005;Di Marzo, 2009). Evidence obtained by multiple groups supports the hypothesis that the CB 1 receptor plays a key role in various cellular events (Ferreira-Vieira et al, 2014;Gomez et al, 2015;Zhang et al, 2015). Moreover, it has been reported that the CB 1 receptor is involved in cognitive and affective processes, as well as in the control of motor activity, stress, addiction, and neuroprotection (Nagayama et al, 1999;Broadbent et al, 2004;Finn, 2010;Naydenov et al, 2014;McReynolds et al, 2016).…”
Section: Cb 1 Receptor: Pharmacology and Cell Signaling Pathwaysmentioning
confidence: 95%
“…Akt may activate mammalian target of rapamycin (mTOR) present in complex 1 (mTORC1), and, in turn, mTORC1 regulates protein synthesis, glucose metabolism, and autophagy. Rapamycin, a mTOR inhibitor, blocks cannabinoid-induced neural progenitor cell proliferation and cannabinoid-enhanced oligodendrocyte differentiation [53, 54]. On the other hand, WIN 55,212-2 decreases mTORC1 activation in prostate cancer cells [55].…”
Section: Endocannabinoid Systemmentioning
confidence: 99%
“…The promotion of oligodendrocyte maturation by 2‐AG was reproduced by administering this endocannabinoid or by impeding its hydrolysis by inhibiting MAGL, inducing OPC proliferation and differentiation in vitro (Bernal‐Chico et al, ; Gómez et al, , , ), and regulating their migration in culture (Sánchez‐Rodríguez et al, ). These effects are mediated through CB1R and CB2R both present on OPCs and mature oligodendrocytes, being the Pi3k‐Akt signaling pathway involved in the promotion of oligodendrocytes differentiation by the endocannabinoid (Gómez et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cannabinoid signaling may enhance the activity of reparative mechanisms, as they can protect OPCs from inflammatory and excitotoxic damage (Bernal‐Chico et al, ; Gómez et al, ; Mecha et al, ; Molina‐Holgado et al, ). In particular, the endocannabinoid 2‐arachidonoylglycerol (2‐AG) promotes the proliferation and differentiation of OPCs (Gómez et al, , , ) and it regulates their migration in culture (Sánchez‐Rodríguez, Gómez, Esteban, García‐Ovejero, & Molina‐Holgado, ). Actually, in vivo studies also demonstrated that inhibiting 2‐AG catabolism through the inhibition of monoacylglycerol lipase (MAGL) or the direct administration of 2‐AG attenuates symptomatology and promotes remyelination in the autoimmune EAE model (Bernal‐Chico et al, ; Hernández‐Torres et al, ; Lourbopoulos et al, ), as well as in the Theiler virus model of MS (Feliu et al, ; Mecha et al, ).…”
Section: Introductionmentioning
confidence: 99%